2006
DOI: 10.1021/bi052076j
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Fibrinogen by Homocysteine Thiolactone Increases Resistance to Fibrinolysis:  A Potential Mechanism of the Thrombotic Tendency in Hyperhomocysteinemia

Abstract: We have previously shown functional differences in fibrinogen from hyperhomocysteinemic rabbits compared to that in control rabbits. This acquired dysfibrinogenemia is characterized by fibrin clots that are composed of abnormally thin, tightly packed fibers with increased resistance to fibrinolysis. Homocysteine thiolactone is a metabolite of homocysteine (Hcys) that can react with primary amines. Recent evidence suggests that Hcys thiolactone-lysine adducts form in vivo. We now demonstrate that the reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 23 publications
5
92
1
2
Order By: Relevance
“…Presence of high level of Hcy can further increase the complex's resistance to fibrinolysis. 36 We previously found that elevated level of Hcy decreased EC layer integrity (defined by changes in transendothelial electrical resistance) suggesting the wider opening of gaps between the ECs. 37 The present data confirmed the results of our other study where we showed that HHcy increased overall pial venular protein leakage but were unable to differentiate paracellular from transcellular transport.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Presence of high level of Hcy can further increase the complex's resistance to fibrinolysis. 36 We previously found that elevated level of Hcy decreased EC layer integrity (defined by changes in transendothelial electrical resistance) suggesting the wider opening of gaps between the ECs. 37 The present data confirmed the results of our other study where we showed that HHcy increased overall pial venular protein leakage but were unable to differentiate paracellular from transcellular transport.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that clots formed from homocysteinylated Fg are more resistant to lysis than clots formed from native Fg. 36,45 Therefore, activation of MMP9 has lesser effect on Fg clots or Fg-Ab complexes during HHcy than during normal level of Hcy. In addition, Hcy potentiates Ab-induced neurodegeneration affecting cytosolic calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans with Duchenne muscular dystrophy did not reveal changes in fibrinogen concentrations (Saito et al 2001). Other authors (Sauls et al 2006) observed that homocysteine thiolactone (HTL) can modify the properties of fibrinogen and disrupt its biological functions through N-homocysteinylation. The results of an in vitro study demonstrated that fibrinogen is easily modified by HTL.…”
Section: Coagulation Profilementioning
confidence: 99%
“…Moreover, lysines are major binding sites for fibrinolystic enzymes and also sites of plasmin cleavage [18][19][20]. Sauls et al [20] suggest that homocysteinylation of lysine residues in fibrinogen may be linked to three important functional consequences.…”
Section: J Malinowska and B Olasmentioning
confidence: 99%
“…Sauls et al [18] have reported the same process, but in their experiments they used rabbit fibrinogen treated only with Hcys, and the authors did not write what form of Hcys was used. Clot structure analysed by scanning electron microscopy showed also no differences in either the general architecture or the fibrin fiber diameter at different Hcys concentrations (13,19, and 52 mM) [17]. However, mass spectrometric analysis of fibrinogen treated with Hcys revealed 12 lysines that were homocysteinylated.…”
mentioning
confidence: 91%